Transhepatic Ipsilateral Right Portal Vein Embolization Extended to Segment IV - Madoff, David (2005)
PURPOSE To analyze outcomes after right portal vein embolization extended to segment IV (right PVE + IV) before extended right hepatectomy, including liver hypertrophy, resection rates, and complications after embolization and resection, and to assess differences in outcomes with two different particulate embolic agents. MATERIALS AND METHODS Between 1998 and 2004, transhepatic ipsilateral right PVE + IV with particles and coils was performed in 44 patients with malignant hepatobiliary disease, including metastases (n = 24), biliary cancer (n = 14), and hepatocellular carcinoma (n = 6). Right PVE + IV was considered if the future liver remnant (FLR; segments II/III with or without I) was less than 25% of the total estimated liver volume (TELV). Tris-acryl microspheres (100–700 μm; n = 21) or polyvinyl alcohol (PVA) particles (355–1,000 μm; n = 23) were administered in a stepwise fashion. Smaller particles were used to occlude distal branches, followed by larger particles to occlude proximal branches until near-complete stasis. Coils were then placed in secondary portal branches. Computed tomographic volumetry was performed before and 3–4 weeks after right PVE + IV to assess FLR hypertrophy. Liver volumes and postembolization and postoperative outcomes were measured. RESULTS After right PVE + IV with PVA particles, FLR volume increased 45.5% ± 40.9% and FLR/TELV ratio increased 6.9% ± 5.6%. After right PVE + IV with tris-acryl microspheres, FLR volume increased 69.0% ± 30.7% and FLR/TELV ratio increased 9.7% ± 3.3%. Differences in FLR volume (P = .0011), FLR/TELV ratio (P = .027), and resection rates (P = .02) were statistically significant. Seventy-one percent of patients underwent extended right hepatectomy (86% after receiving tris-acryl microspheres, 57% after receiving PVA). Thirteen patients (29%) did not undergo resection (extrahepatic spread [n = 9], inadequate hypertrophy [n = 3], other reasons [n = 1]). No patient developed postembolization syndrome or progressive liver insufficiency after embolization or resection. One death after resection occurred as a result of sepsis and hemorrhage. Median hospital stays were 1 day after right PVE + IV and 7 days after resection. CONCLUSION Transhepatic ipsilateral right PVE + IV with use of particles and coils is a safe, effective method for inducing contralateral hypertrophy before extended right hepatectomy. Embolization with small spherical particles provides improved hypertrophy and resection rates compared with larger, nonspherical particles.